A Genealogical Account of the Royal House of Bruce (Proceedings of the Society of Antiquaries of Scotland, 1855)
Mr Surenne traced the genealogy of Robert Bruce's descendants through twenty generations, identifying notable members of the family from Scotland, England, Norway and Denmark.  Meeting notes for March 27, 1854 are appended.